UPAYA PENINGKATAN KERAGAMAN PRODUK MELALUI PENGEMBANGAN PENGAMBILAN RISIKO BERINOVASI (Proceeding Fakultas Ekonomi, 2013)
This research aims to develop a new theoretical approach in solving the relationship between risk taking with the marketing environment to learn and analyze the development process of risk taking, andlater risk taking innovation influences towards the diversity of the product. The research was conducted at the district and municipality of Pekalongan in Central Java Province. The empirical test model usedwas Structural Equation Modeling (SEM). The sample size of the research was 200 owners/ leaders/managers of Small and Medium Scale Enterprises based on the consideration as the person mostresponsible and accountable in managing Small and Medium Enterprises (SMEs) better overall problem of capital, marketing, and human resources. The result showed that adaptibility to marketingenvironment, knowledge of marketing strategy, and employees working skill affects positively towards risk taking innovation. The result of the study also showed that risk taking innovation influencespositively towards the diversity of the product. This research incorporates Resources Based Theory, and Prospect Theory. The limitation and implication for the future study and the managerial implication arealso discussed in this study.Keywords: Adaptibility to marketing environment, competence, risk taking innovation, innovation diversity